A practical guide to analyzing the force-time curve of isometric tasks in Excel - Chavda, S.; Turner, A. N.; Comfort, P.; Haff, G. G.; Williams, S.; Bishop, C.; Lake, J. (Strength and Conditioning Journal, 2020)
Understanding force generating capabilities of athletes is an important facet of strength diagnostics. The use of isometric tasks such as the isometric squat and isometric midthigh pull are therefore popular methods used to gain a deeper understanding as to what strength characteristics have changed over a given period. This article aims to provide information on how to understand and analyse the force-time curve of isometric tasks in microsoft excel, thus providing practitioners an inexpensive and accessible alternative to readily available software on the market.